Zeitschrift für Ägyptische Sprache und Altertumskunde (De Gruyter (A), 1863)
The Zeitschrift für Ägyptische Sprache und Altertumskunde, the oldest Egyptological journal, covers the whole field of Egyptology including Demotic, Coptic and Meroitic studies. The contributions examine the language, history, religion, art, and material culture of the ancient Nile valley. In addition, they deal with the history of Egyptology and with Egypt's influence on contemporary and later cultures.